The best of Lori Wick [large type] : a gathering of hearts - Wick, Lori (Thorndike Press large print Christian romance, 2010)
A collection of two- to three-page excerpts from Wick's novels, grouped by concept and each ending with a Biblical passage, to evoke sweet memories of joy, family, love, and faith.